Invasive cervical cancer in HIV-infected women in low-income countries: experience from Côte d’Ivoire - N’guessan, Edouard; Toure, Moctar; Dia, Jean-Marc; Gbeli, Franck; Guie, Privat (Nepal Journal of Obstetrics and Gynaecology, 2019)
Aims: To assess experience in the management of invasive cervical cancer in HIV- infected women in a sub-medical setting. Methods: Retrospective cohort study of patients with cervical cancer at the University Hospital of Treichville between 2012 and 2016. The association between HIV infection and epidemiological data was investigated using the chi-square test. Survival data were calculated according to the Kaplan-Meier method. Results: A total of 99 women with cervical cancer were included in the study; 49 (49.5%) of whom were HIV positive. The average age of patients was 51.5 years. HIV testing was performed in 53.1% after the diagnosis of cancer. Virtually all (98%) of women living with HIV had received antiretroviral therapy. Their median CD4 was 382 elements / ml. HIV infected Women were significantly younger than HIV-negative women. The median survival rate for patients living with HIV was 9.6 months Versus 15 months for HIV-negative patients. HIV infection was associated with a significant increase in deaths and a shorter survival among patients with cervical cancer. Conclusions: Cervical cancer is more aggressive in HIV infected women. Overall survival was significantly shorter when the patients were infected with HIV.